2004
DOI: 10.1128/aem.70.11.6871-6874.2004
|View full text |Cite
|
Sign up to set email alerts
|

Electric Current-Induced Detachment of Staphylococcus epidermidis Biofilms from Surgical Stainless Steel

Abstract: Biomaterial-centered infections of orthopedic percutaneous implants are serious complications which can ultimately lead to osteomyelitis, with devastating effects on bone and surrounding tissues, especially since the biofilm mode of growth offers protection against antibiotics and since removal frequently is the only ultimate solution. Recently, it was demonstrated that as a possible pathway to prevent infections of percutaneous stainless steel implants, electric currents of 60 to 100 A were effective at stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 23 publications
(23 reference statements)
8
100
1
1
Order By: Relevance
“…The same group would later show that DC current applied for 6 h was much more effective at detaching 200 minute biofilms (grown on the electrode surface by circulating tryptic soy broth for 200 minutes following the aforementioned rinsing of planktonic bacteria with buffer) from stainless steel surfaces than AC applied for the same duration [65]. Results have demonstrated that direct currents are effective at and much better than alternating currents for detaching Staphylococcus epidermidis biofilms on orthopedic implants.…”
Section: Bacterial Surface Detachment Using Electric Currentsmentioning
confidence: 75%
See 2 more Smart Citations
“…The same group would later show that DC current applied for 6 h was much more effective at detaching 200 minute biofilms (grown on the electrode surface by circulating tryptic soy broth for 200 minutes following the aforementioned rinsing of planktonic bacteria with buffer) from stainless steel surfaces than AC applied for the same duration [65]. Results have demonstrated that direct currents are effective at and much better than alternating currents for detaching Staphylococcus epidermidis biofilms on orthopedic implants.…”
Section: Bacterial Surface Detachment Using Electric Currentsmentioning
confidence: 75%
“…Limitations of conductive polymers are generally due to manufacturing costs, material variation, toxicity, poor solubility in solvents and inability to directly melt the polymer. However, when used as a very thin surface layer on a catheter for example [102], they are as effective as indium tin oxide [65]. Composite materials such as silicones mixed with silver or nickel particles could offer the best possible solution at present for implementing some of the most promising recent electrical bacterial control strategies in an IMD [30,69,85] Silver nanoparticles embedded in a polymer matrix deposited using plasma polymerization could form a conductive polymer with inherent antibacterial properties [103].…”
Section: Five-year Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be the result of disruption of the biofilm to release bacteria in the more vulnerable planktonic form or through a molecular or microenvironmental mechanism that is currently unknown. Although there have been numerous in vitro reports on the antimicrobial effects of direct electrical simulation with or without combination with antibiotics [3,6,8,9,17,18,24], there are only a few in vivo reports [7,13,23]. In contrast to the other in vivo models using electrical stimulation to treat implant-associated infections [7,13,23], CVCES uses a three-electrode configuration that allows us to precisely control the cathodic potential of the titanium implant [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the extensive use of antibiotics holds a threat in the future due to the rapid rise of multi drug resistant bacteria. Recently, a number of alternative modes like weak electric currents [1,2,3,4], ultrasound wave therapy [5,6,7] , thermotherapy [8], photodynamic therapy [9] have been studied. These are expected to aid the antibiotics in the battle against bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%